TINJAUAN KEPUASAN KERJA KARYAWAN DI GRAND ROCKY HOTEL BUKITTINGGI - Hervina, Hervina; Kasmita, Kasmita; Suyuthie, Hijriyantomi (Journal of Home Economics and Tourism, 2015)
This purpose of research is to describe job satisfaction of employees in Grand Rocky Hotel Bukittinggi. This research consists of five indicators of job satisfaction are: payroll, the work itself, promotion, supervision, and relationships with co-workers. This type of research is quantitative descriptive, the population in this research are 114 people’s. Sampling technique is proportional sampling. Sample number in this research amounted for 54 people’s. Data collection using a questionnaire based on a Likert scale that has been tested for validity and reliability. Furthermore, the data were analyzed by categorization rating based on the average scores and percentage assessment. Results of this research concluded that overall job satisfaction of employees in the Grand Rocky Hotel Bukittinggi is classified in the category very well with the average value of 173,5 in the range scores of ≥172 and interpretation percentage 56 %. Regard: Job Satisfaction, Employee1Prodi